Repositioning Oligarchy and Democratic Governance: Institutional Reform in Indonesia - Muhamad Fajar Pramono; Asyifa Nadia Jasmine; Samra Naz; Halimah Abdul Manaf; Dyah Mutiarin (Jurnal Ilmiah Peuradeun, 2026)
Good governance remains a central ideal in democratic systems; however, its substantive realization in Indonesia continues to be constrained by the persistent dominance of oligarchic power, which existing studies largely frame as a pathological threat to democracy rather than an institutionally governed phenomenon. Addressing this gap, this study examines how oligarchic power can be repositioned within a framework of democratic governance through a neo-institutionalist perspective that treats oligarchy as an institutionally conditioned form of power. Using qualitative policy analysis, this research analyzes political financing, public policy formulation, and institutional reform through document analysis, regulatory review, and comparative policy evaluation. The findings show that oligarchic dominance is reproduced through weak institutional constraints, fragmented accountability mechanisms, and limited public oversight, yet can be systematically constrained through strengthened regulatory frameworks, credible law enforcement, and expanded participatory governance. By proposing the concept of repositioning oligarchy as an institutional strategy, this study contributes to governance studies, both theoretically and practically, by offering policy-relevant insights for improving democratic governance in Indonesia and other emerging democracies facing similar political–economic challenges.